Optimal Investment with Stock Repurchase and Financing as Signals - Constantinides, George M.; Grundy, Bruce D. (Review of Financial Studies, 1989)
[When management has private information it has an incentive to finance investment by issuing a security that is overpriced in the market. The market's valuation of the issued security may lead management either to forego profitable investments or to invest suboptimally. With investment fixed, there exist fully revealing signaling equilibria in which the covenants of the issued claim serve as signals. A straight bond issue cannot provide the signals but a convertible bond issue can. With investment endogenous, fully revealing equilibria exist in which the par value of a straight bond issue and the announced level of investment jointly serve as signals and investment is optimal. The article also investigates the role of a stock repurchase in these equilibria.]